2017
DOI: 10.1016/j.fcr.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Is maize-cowpea intercropping a viable option for smallholder farms in the risky environments of semi-arid southern Africa?

Abstract: Intercropping cereals with legumes can potentially enhance productivity and soil fertility. There is limited experimental evidence on the mechanisms underlying benefits or risks in intercropping systems and belowground interactions in intercrops remain largely unstudied. Such understanding can inform strategies towards maximising returns to investments, particularly in poor fertility soils on smallholder farms in semi-arid areas of sub-Saharan Africa. Additive intercropping experiments were established coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 36 publications
5
41
1
4
Order By: Relevance
“…The correlation of maize yield with soil fertility parameters supports previous suggestions by Vanlauwe et al (2014) that additional fertilizer application would be a necessary element of CA, to ensure that sustainability and profitability go hand in hand. Contrary to findings by Masvaya et al (2017) with maize-cowpea intercropping, the yields in the current study were generally not improved and were often even reduced when maize was intercropped with a legume, despite improvements in soil nitrogen concentration compared to conventional practice (measured after 4 years). Poor soil fertility and low addition of nutrients through poor-quality manure, in combination with increased interspecific competition, may have masked the positive effects of cover crops on maize yields.…”
Section: Correlation Between Crop Production and Soil Fertility Or Stcontrasting
confidence: 99%
“…The correlation of maize yield with soil fertility parameters supports previous suggestions by Vanlauwe et al (2014) that additional fertilizer application would be a necessary element of CA, to ensure that sustainability and profitability go hand in hand. Contrary to findings by Masvaya et al (2017) with maize-cowpea intercropping, the yields in the current study were generally not improved and were often even reduced when maize was intercropped with a legume, despite improvements in soil nitrogen concentration compared to conventional practice (measured after 4 years). Poor soil fertility and low addition of nutrients through poor-quality manure, in combination with increased interspecific competition, may have masked the positive effects of cover crops on maize yields.…”
Section: Correlation Between Crop Production and Soil Fertility Or Stcontrasting
confidence: 99%
“…The general decline of grain yields with increased duration of experimentation observed at all sites could partially be explained by differences in seasonal rainfall patterns. However, Masvaya et al (2017) suggest that this could be due to reduced N mineralization because of minimum soil disturbance and mulching practices under NT systems.…”
Section: Effect Of Different Residue Levels and N On Maize Yieldmentioning
confidence: 99%
“…This suggests that a smallholder farmer achieves no additional grain yield gain with 90 kg N ha −1 and they can therefore target 30 kg N ha −1 investment in mineral fertilizer. In a mulched NT system under semiarid conditions, a study by Masvaya et al (2017) showed that 40 kg N ha −1 gives the highest yield with above average seasonal rainfall. Under sub-humid conditions of Kenya, results from Kitonyo et al (2018) showed that 80 and 120 kg N ha −1 give similar maize yield under 3 and 5 t ha −1 soil cover.…”
Section: Effect Of Different Residue Levels and N On Maize Yieldmentioning
confidence: 99%
“…Currently, in both rotational and intercropping systems, the adoption of legumes is largely discouraged due to poor establishments of the legume component. In rotation, legumes are commonly grown utilizing residual soil moisture remaining during the dry season, and with no additional fertilization, whilst in intercropping systems, the planting of a legume companion is delayed in order to avoid shading and competition (Masvaya et al 2017). Therefore, on-farm seed priming may ameliorate these unfavourable planting conditions and boost the benefits of cereal-legume cropping systems, e.g.…”
Section: Plant Typementioning
confidence: 99%